Polimorfismo XmnI e haplótipos do gene beta globina e suas relações com os níveis de hemoglobina Fetal em beta talassemia - Chinelato, Isabela Sandrin [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The beta thalassemia are frequent genetic disorders and sufferers may have increased levels of hemoglobin A2 (Hb A2) and fetal hemoglobin (Hb F). The mutations present in individuals may be associated with different haplotypes of β–globin grouping. The objectives of this study consisted in investigating the frequencies of the XmnI polymorphism (-158 CT) and the pattern of the β-globin haplotypes in heterozygous and homozygous individuals for beta thalassemia, relate them to the levels of Hb F, and compare them with individuals without hemoglobinopathies. We analyzed 150 samples from heterozygous individuals with beta thalassemia, 22 homozygous and 150 individuals without hemoglobinopathies (control group). All samples were tested for classical hemoglobinopathies diagnosis and molecular analyzes Allele Specific PCR (AE-PCR) to confirm the mutation of beta thalassemia and PCR length polymorphism restriction fragment (PCR-RFLP) for identification of the polymorphism XmnI and sites of the β-globin haplotypes. Statistical tests were performed using STATISTICA 8.0 and Haploview 4.2 software. In beta thalassemia heterozygous individuals, mutation CD39 was the most common (62%) and in homozygous was the IVS-I-6 (22 %). We observed a significant difference in the levels of Hb F among the unidentified mutations and IVS-I-110 (p<0.05) in heterozygous individuals. The presence of the XmnI polymorphism was observed in all groups, but only heterozygous individuals for beta thalassemia was statistical difference in relation to increased levels of Hb F (p = 0.007). In the three groups were observed haplotype patterns I, II, IV, VI, VII and IX. For individuals heterozygous to beta thalassemia, the patterns II (24.3 %) and VII (32 %) were the most frequent, for individuals with beta thalassemia homozygous, the patterns I (29.5 %) and VII (38.6 %) and individuals without hemoglobinopathies, the patterns I (31%) and VII (28.3%). There was ...

As talassemias do tipo beta são afecções genéticas frequentes na população mundial e seus portadores podem apresentar elevação nos níveis de hemoglobina A2 (Hb A2) e hemoglobina fetal (Hb F). As mutações presentes nos indivíduos podem estar associadas a diferentes haplótipos do grupamento da β-globina. Os objetivos do trabalho consistiram em investigar as frequências do polimorfismo XmnI (-158 CT) e do padrão de haplótipos da β-globina em indivíduos heterozigotos e homozigotos para a beta talassemia, relacioná-las com os níveis de Hb F, e compará-las com indivíduos sem hemoglobinopatias. Foram analisadas 150 amostras de indivíduos beta talassêmicos heterozigotos; 22 de indivíduos homozigotos e 150 de indivíduos sem hemoglobinopatias (grupo controle). Todas as amostras foram submetidas aos testes clássicos de diagnóstico de hemoglobinopatias e à análises moleculares por PCR Alelo Específico (PCR-AE) para confirmação da mutação de beta talassemia, e PCR para polimorfismos de comprimento de fragmentos de restrição (PCR-RFLP) para a identificação do polimorfismo XmnI e dos sítios de haplótipos da β-globina. Os testes estatísticos foram realizados com o software STATISTICA 8.0 e Haploview 4.2. Nos indivíduos beta talassêmicos heterozigotos, a mutação CD39 foi a mais frequente (62%) e nos homozigotos, a IVS-I-6 (22%). Foi observada diferença significativa nos níveis de Hb F entre os indivíduos que possuem mutações ainda não identificadas, em relação aos que possuem a mutação IVS-I-110 (p<0,05), no grupo de heterozigotos. A presença do polimorfismo XmnI foi observada em todos os grupos estudados, porém, somente para os indivíduos com talassemia beta heterozigota houve diferença estatística em relação aos níveis aumentados de Hb F (p=0,007). Nos três grupos foram observados os padrões típicos de haplótipos I, II, IV, VI, VII e IX. Para os indivíduos com beta talassemia ...
Keywords: Genetica humana; Talassemia; Hemoglobinopatia; Polimorfismo (Genética); Thalassemia